2022
DOI: 10.1158/1078-0432.ccr-22-0444
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive EGFRvIII Detection in Circulating Extracellular Vesicle RNA of Glioma Patients

Abstract: Purpose: Liquid biopsy offers an attractive platform for noninvasive tumor diagnosis, prognostication, and prediction of glioblastoma clinical outcomes. Prior studies report that 30% to 50% of GBM lesions characterized by EGFR amplification also harbor the EGFRvIII mutation. Experimental Design: A novel digital droplet PCR (ddPCR) assay for high GC content amplicons was developed and optimized for sensitive detection of EGFRv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It is important to note that EGFRvIII is one of the few tumor-specific antigens in GBM known to date and one that has been demonstrated to be safe as a CAR T cell target in clinical GBM studies 10,34 . Yet, antigen escape might pose a threat to all EGFRvIII-targeted treatments 65 , underscoring the need for careful patient stratification using reliable pre-therapeutic plasma 66 or tissue biopsy analysis to confirm the presence of this oncogenic mutation also in recurrent GBM. Importantly, recent studies using more sensitive methods of detection, suggest that even up to 70% of GBM patients express EGFRvIII 66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that EGFRvIII is one of the few tumor-specific antigens in GBM known to date and one that has been demonstrated to be safe as a CAR T cell target in clinical GBM studies 10,34 . Yet, antigen escape might pose a threat to all EGFRvIII-targeted treatments 65 , underscoring the need for careful patient stratification using reliable pre-therapeutic plasma 66 or tissue biopsy analysis to confirm the presence of this oncogenic mutation also in recurrent GBM. Importantly, recent studies using more sensitive methods of detection, suggest that even up to 70% of GBM patients express EGFRvIII 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, antigen escape might pose a threat to all EGFRvIII-targeted treatments 65 , underscoring the need for careful patient stratification using reliable pre-therapeutic plasma 66 or tissue biopsy analysis to confirm the presence of this oncogenic mutation also in recurrent GBM. Importantly, recent studies using more sensitive methods of detection, suggest that even up to 70% of GBM patients express EGFRvIII 66 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the main obstacles in detecting glioma from plasma EVs is the isolation and quantification of tumor‐derived EVs from a heterogenous background. While techniques have sought to amplify detection through enrichment and modification of downstream analytes, [ 34 ] it is also important to establish the baseline capacities of the explored processing methods. We have found that the recovery of tumor‐derived EVs from a healthy plasma EV background, as defined by EGFRvIII capture in IMEX and EGFRvIII RNA quantification in ddPCR, follows the patterns of analyte isolation identified in in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…Using the 2 –ΔΔCt technique and β -actin as the reference gene, the mRNA expression of each gene was evaluated. The primer used for GCSF (Forward Primer GTGCCACCTACAAGCTGTGC and Reverse Primer AAAGGCCGCTATGGAGTTGG) and GCSFR (Forward Primer AAGAGCCCCCTTACCCACTACACCATCTT and Reverse Primer TGCTGTGAGCTGGGTCTGGGACACTT), STAT3 (Forward Primer CATATGCGGCCAGCAAAGAA and Reverse Primer ATACCTGCTCTGAAGAAACT) and for β –actin (Forward Primer CATGTACGTTGCTATCCAGGC and Reverse Primer CTCCTTAATGTCACGCACGAT) 18 , 19 .…”
Section: Methodsmentioning
confidence: 99%